Caracterização de sintomas de deficiência de boro em pepino (Cucumus sativus L.) na fase de frutificação - Ribeiro Calbo, Maria Elisa; Monnerat, Pedro Henrique; Shimoya, Chotaro (Revista Ceres, 2025)
The objective of the experiment was to describe the boron deficient symptoms in cucumber (Cucumis sativum L.) as well as the enatomical modifications in the deficient fruit. Sixteen plants were cultivated in a modified Johnson's nutrient solution. Plants with 45 and 53 days of age were transferred to a boron deficient solution. All the fruits were harvested 20 days after the pollination. The fruits produced from boron dificient plants showed irregular watery areas (edematous) with areas of normal green color in their centers. These watery areas acquired a resinous aspect with a yellow translucent color and later became dehydrated, depressed, and rough-surfaced. The surface of the fruit was covered with small protuberances. There was a reduction in the size of the seeds and in the weight of the fruits. Anatomically, the cuticle was almost absent in the boron deficient fruits and the epidermal cells were reduced in size. The parenchyma was compact with greatly restricted intercellular spaces; the size and shape of the cells were irregular, the nucleus was enlarged and discolored and the cell walls were thin.